A Cyclized Polyacrylonitrile Anode for Alkali Metal Ion Batteries. Issue 3 (16th November 2020) - Zhang, Wenli; Sun, Minglei; Yin, Jian; Abou‐Hamad, Edy; Schwingenschlögl, Udo; Costa, Pedro M. F. J.; Alshareef, Husam N.
Abstract: Organic anodes have attracted increasing attention for alkali metal ion batteries. In this work, we discovered that cyclized polyacrylonitrile (cPAN) can serve as an excellent anode for alkali metal ion batteries. Upon activation cycling, as an anode of lithium‐ion battery, cPAN exhibits a reversible capacity as high as 1238 mAh g −1 under a current density of 50 mA g −1 . Based on electrochemical experiments and first‐principles calculations, it is demonstrated that the hexagonal carbon ring, piperidine ring, and pyridine nitrogen in ladder cPAN are the main active sites for lithium‐ion storage. cPAN displays a unique potential‐dependent solid electrolyte interphase formation from 0.1 to 0.01 V vs. Li/Li + . It also displays decent performance as an anode in SIBs and PIBs. Abstract : Cyclized polyacrylonitrile is developed as an efficient anode material for alkali metal (Li, Na, and K) ion batteries. This organic anode exhibits high capacity and long cycle life. The discovery of cyclized polyacrylonitrile anode paves the way to new organic anodes for rechargeable batteries.